Assessment of agarwood hydrodistillation byproduct for consumable potential - Mohamad Kahar, Ernna Erynna (2023)
Agarwood hydrosol is a by – product of the hydrodistillation process in the extraction of essential oil usually being underutilized although some consumers believe that all components of agarwood have health benefits. To enhance the value of hydrosol in the market, three (3) formulations were designed based on different type of sugar used; F1 (white sugar), F2 (brown sugar) and F3 (white sugar + brown sugar) which hydrosol was used as main ingredient. To determine the sweetened agarwood drink (SAD) characteristics and preferences, this project undergone analyses; sensory, physicochemical, antioxidant, cytotoxicity and enumeration of yeast and mold for shelf – life analysis according to AOAC method and Malaysian Food Regulation (1985). The data summarized that drink obtained dislike perception. The characteristics of SAD was acidic (pH 4.42), viscosity (2.14 m.Pa.s), ash (0.31 g), protein (1.23g), carbohydrate (9.26 %) and sugars (12.28 %), no fat, contain sodium, potassium, zinc, magnesium and calcium at the same time no heavy metals were detected. However, low antioxidant properties exerted on drinks; DPPH activity (32.54%), FRAP (0.73 mmol Fe2+ E/L), TPC (0.2 mg GAE/ml) while TFC (2.28mg RE/ml). Weak correlation between DPPH, TPC and TFC which R2 = 0.49 and 0.56 respectively and no correlation between FRAP to TPC and TFC. Cytotoxicity analysis on brine shrimp was 100% mortality. Shelf–life analysis showed no yeast or mold growth in drinks. Overall, formulations made to SAD did not obtained panellist acceptability but increase the product physicochemical properties. This drink lack of antioxidant value, and brine shrimp assay did not suitable for drink toxicity analysis because control drink also resulted 100% mortality. Addition of preservatives in drink formulation prolong the shelf life of drink to more than 1 ½ years storage